Comparative immunohistochemical study of Bcl-X in ameloblastoma, keratocystic odontogenic tumor and adenomatoid odontogenic tumor - Shukla, Payal (J Oral Maxillofac Pathol, 2017)
OBJECTIVES: Since its recognition as a physiologic process associated with tumor, among molecular mechanisms involved in tumor progression, defects in regulation of apoptosis have generated an accelerating volume of research that has sought to elucidate the role of programed cell death in pathogenesis and treatment of various tumors. Therefore, this study was performed to understand better the diverse biological profile of epithelial odontogenic tumors with the help of immunohistochemical expression of Bcl-X protein. MATERIALS AND METHODS: We studied Bcl-X protein expression in 45 cases of epithelial odontogenic tumors which included 15 cases each of ameloblastomas, keratocystic odontogenic tumor (KCOT) and adenomatoid odontogenic tumor (AOT) and correlated the expression with their growth pattern. RESULTS: Cytoplasmic staining of Bcl-X revealed overexpression in ameloblastoma when compared to KCOT and AOT. Percentage of positive cells showed a statistically significant difference, P = 0.007 between ameloblastoma and KCOT, whereas P < 0.001 between ameloblastoma and AOT. However, no significance was observed between KCOT and AOT (P = 0.132). CONCLUSION: The present study supports the fact that epithelial odontogenic tumors show diverse growth profiles. An increased Bcl-X expression was seen in ameloblastoma compared to KCOT and least expression in case of AOT which could be indicative of more aggressive biological behavior and increased cell survival activity of ameloblastoma than KCOT and AOT. This signifies the diagnostic relevance of this biomarker and also could be a possible regulator of the proliferative compartment by contributing in tumor progression and cytodifferentiation of epithelial odontogenic tumors.